Stromal biology and therapy in pancreatic cancer. Issue 6 (21st October 2010) - Neesse, Albrecht; Michl, Patrick; Frese, Kristopher K; Feig, Christine; Cook, Natalie; Jacobetz, Mike A; Lolkema, Martijn P; Buchholz, Malte; Olive, Kenneth P; Gress, Thomas M; Tuveson, David A
Abstract : Pancreatic ductal adenocarcinoma (PDA) is an almost uniformly lethal disease. One explanation for the devastating prognosis is the failure of many chemotherapies, including the current standard of care therapy gemcitabine. Although our knowledge of the molecular events underlying multistep carcinogenesis in PDA has steadily increased, translation into more effective therapeutic approaches has been inefficient over the last several decades. Evidence for this innate resistance to systemic therapies was recently provided in an accurate mouse model of PDA by the demonstration that chemotherapies are poorly delivered to PDA tissues because of a deficient vasculature. This vascular deficiency correlated with the presence of a dense stromal matrix that is a prominent histological hallmark of PDA tumours. Therapeutic targeting of stromal cells decreased the stroma from pancreatic tumours, resulting in increased intratumoral perfusion and therapeutic delivery of gemcitabine. Stromal cells contained within the PDA tumour microenvironment therefore represent an additional constituent to neoplastic cells that should be critically evaluated for optimal therapeutic development in preclinical models and early clinical trials.